Traveling public innovation laboratories. Knowledge management strategy in public administration to strengthen public-territorial spheres. - Tapia Góngora, Edwin Manuel (2025)
The loss of confidence in the governments and democracy of the Latin American region (Latinobarómetro, 2023) has made visible the limits of public management based only on technocratic consensus. The need rises to seek new paths that simultaneously allow overcoming recurrent public problems and contribute to improving the legitimacy and confidence in the capacity of public administrations and governments. In November 2022, at the Valledupar headquarters of the Higher School of Public Administration (ESAP) of Colombia, at the Territorial Center in Public Administration (CETAP), a forum was held about poverty in the region. This space did not only shed light on the social programs established before, during and after the COVID-19 pandemic, but also raised questions about the connection between the effectiveness of public innovation and the legitimacy of these programs. This article systematizes the implementation experience of the first phase of the Itinerant Innovation Laboratory at CETAP Valledupar, which took place between November 2022 and September 2024. The document is divided into five parts: Introduction, methods and materials, results, discussion and conclusion. The methods include the spatial and temporal scope and analysis variables; in the results, the generated products are presented; in the discussion, a reflection on the political dimension of public innovation is presented, and; in the conclusions, some challenges are stated in knowledge management for public innovation in contexts marked by patrimonialism and depoliticization of the state public spheres.